A method for preparing a carbon fiber paper for electromagnetic shielding and a carbon fiber paper

CN122899080APending Publication Date: 2026-10-13GUANGDONG GUANHAO NEW MATERIALS R&D CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611235499.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0007]为了解决现有技术中存在的因添加绝缘性聚合物粘结剂导致导电性显著下降,同时碳纤维纸的MD/TD方向定量均一性差,导电填料与纤维基体结合不牢固导致导电网络不稳定的技术问题,本发明提供用于电磁屏蔽的碳纤维纸的制备方法,以及一种用于电磁屏蔽的碳纤维纸,通过阶梯式酶处理使碳素逐轮嵌入纤维沟槽,形成无粘结剂阻断的直接导电通路,同时利用楔形流道剪切诱导碳素定向排列,提升导电网络连续性;在避免绝缘粘结剂导电损失的同时,改善了纤维分散匀度

Benefits of technology

[0020]本发明提供的用于电磁屏蔽的碳纤维纸的制备方法,通过“阶梯式酶处理循环+楔形流道剪切诱导定向排列”的协同工艺设计,取得了以下有益效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122899080A_ABST
    Figure CN122899080A_ABST
Patent Text Reader

Abstract

The application discloses a kind of carbon fiber paper for electromagnetic shielding and preparation method thereof.To solve the problem that carbon fiber paper is not good in conductivity, MD / TD direction quantitative uniformity is poor, and the combination of conductive filler and fiber matrix is not firm, leading to unstable conductive network.The carbon fiber paper for electromagnetic shielding comprises: carbon fiber as skeleton material;Regenerated cellulose fiber as skeleton reinforcing material;And microfibrillated carbon is filled in the groove on the surface of the regenerated cellulose fiber to form a conductive path;The microfibrillated carbon is at least partially embedded in the groove inside the regenerated cellulose fiber, and is arranged in the axial direction of the regenerated cellulose fiber.The application can improve the continuity of conductive network;While avoiding the conductive loss of insulating adhesive, the uniformity of fiber dispersion is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electromagnetic shielding materials technology, and more specifically, to a method for preparing carbon fiber paper for electromagnetic shielding, and a carbon fiber paper for electromagnetic shielding. Background Technology

[0002] Carbon fiber paper, with its advantages of porous structure, high porosity, good conductivity, high temperature resistance, and corrosion resistance, is the most widely used base layer material for electromagnetic shielding paper, and can meet the requirements of electromagnetic shielding paper for conductive network skeleton and performance.

[0003] However, existing carbon fiber paper has the following problems in its preparation process: On the one hand, in order to improve the basis uniformity of carbon fiber paper in the MD / TD directions and achieve a more continuous and complete three-dimensional conductive network structure, existing methods typically employ latex coating processes to enhance coating uniformity during the manufacturing of electromagnetic shielding paper. However, due to limitations in equipment design and latex dilution issues, the uniformity and basis uniformity remain poor, making it difficult to meet the requirements of high-precision electromagnetic shielding applications.

[0004] On the other hand, existing processes typically improve the mechanical properties of carbon fiber paper by adding polymer binders. However, polymer binders are usually insulators, and their addition significantly sacrifices the conductivity of the carbon fiber paper. For demanding electromagnetic shielding applications, such as precision instruments, electronic components, and military applications, the conductivity of existing carbon fiber paper remains insufficient to meet requirements.

[0005] To address the aforementioned issues, existing technologies disclose methods for activating plant fibers with cellulase to improve fiber dispersibility (e.g., CN115287941B). However, this method employs a single-step enzymatic treatment and requires high-temperature graphitization, resulting in a complex and energy-intensive process. Furthermore, the carbon-based filler and fiber are only macroscopically blended, leading to weak bonding and a discontinuous conductive network. Other solutions utilize a composite layered film formed from plant fibers and various carbon-based fillers (e.g., CN121653998A), but this method uses interfacial crosslinking agents and flexible buffer polymers for assisted bonding. The crosslinking agent, acting as an insulating component, still negatively impacts conductivity.

[0006] Therefore, there is an urgent need in the field for a method for preparing carbon fiber paper that can improve the uniformity and basis weight of carbon fiber paper, enhance its conductivity, and eliminate the need for adding insulating binders or crosslinking agents. Summary of the Invention

[0007] To address the technical problems in existing technologies, such as a significant decrease in conductivity due to the addition of insulating polymer binders, poor quantitative uniformity of carbon fiber paper in the MD / TD direction, and unstable conductive networks caused by weak bonding between conductive fillers and the fiber matrix, this invention provides a method for preparing carbon fiber paper for electromagnetic shielding, and a carbon fiber paper for electromagnetic shielding. The method involves a step-by-step enzymatic treatment that allows carbon fibers to be embedded into fiber grooves in successive cycles, forming direct conductive pathways without binder blockage. Simultaneously, wedge-shaped flow channels are used to shear and induce the directional alignment of carbon fibers, improving the continuity of the conductive network. This approach improves fiber dispersion uniformity while avoiding conductive loss due to insulating binders.

[0008] In a first aspect, the present invention provides a method for preparing carbon fiber paper for electromagnetic shielding, comprising: Regenerated cellulose fibers are mixed with microfibrillated carbon to obtain a mixed slurry; The mixed slurry is subjected to a stepwise enzymatic treatment, which includes N cycles of enzymatic treatment and carbon filling, where N ≥ 2, and each cycle includes: The regenerated cellulose fibers were treated with endonuclease to expose carboxyl and hydroxyl groups on the surface of the regenerated cellulose fibers. After the endonuclease treatment, microfibrillated carbon is added to the system so that the microfibrillated carbon is embedded in the grooves on the surface of the regenerated cellulose fibers. The mixed slurry after the stepwise enzyme treatment is fed into a wedge-shaped channel, where the gradient-enhanced shear force causes the microfibrillated carbon to align along the axial direction of the regenerated cellulose fibers. The mixed slurry, after being treated with a wedge-shaped flow channel, is mixed with carbon fiber slurry, then formed, dried, and hot-pressed to obtain carbon fiber paper for electromagnetic shielding.

[0009] Furthermore, in the stepwise enzyme treatment, the enzyme concentration increases in each round from the first to the Nth round, the treatment time decreases in each round, and the concentration of microfibrillated carbon added after each round of enzyme treatment increases in each round.

[0010] Furthermore, the stepwise enzyme treatment comprises three cycles: Round 1: Enzyme concentration is 0.5 to 1.0 U / mL, treatment temperature is 25±2℃, treatment time is 10 to 15 min, pH is 5.0 to 5.5, after enzyme treatment, add microfibrillated carbon to a concentration of 0.5 wt%, and fill time is 30±3 min; Round 2: The enzyme concentration is 2.0 to 3.0 U / mL, the treatment temperature is 30±2℃, the treatment time is 7 to 10 min, the pH is 4.8 to 5.2, and after enzyme treatment, microfibrillated carbon is added to a concentration of 1.0 wt%, with a filling time of 20±3 min. Round 3: Enzyme concentration of 5.0 to 8.0 U / mL, treatment temperature of 35±2℃, treatment time of 5 to 7 min, pH of 4.5 to 4.8, after enzyme treatment, add microfibrillated carbon to a concentration of 1.5 wt%, and fill time of 10±3 min.

[0011] Furthermore, prior to the stepwise enzyme treatment, a step of regulating the zeta potential in stages is included, comprising: First stage: The regenerated cellulose fiber is pretreated with enzymes to expose carboxyl and hydroxyl groups on the surface of the regenerated cellulose fiber, thus imparting a weak negative charge. Second stage: The microfibrillated carbon is adjusted to near its isoelectric point using a surfactant, so that it is in a critical state of slight flocculation. Then, the regenerated cellulose fibers treated in the first stage are mixed with the microfibrillated carbon fibers treated in the second stage.

[0012] Furthermore, the surfactant is a bio-based cashew sulfonate.

[0013] Furthermore, the spacing of the wedge-shaped channels gradually changes from wide to narrow. When the mixed slurry flows through the wedge-shaped channels, it is subjected to a gradient-enhanced shear force, causing the microfibrillated carbon to be oriented along the axial direction of the regenerated cellulose fibers, forming an axially parallel structure.

[0014] Furthermore, the regenerated cellulose fiber is a robust fiber used as a reinforcing skeleton; the microfibrillated carbon is a highly swellable carbon used as a conductive matrix.

[0015] In a second aspect, the present invention provides a carbon fiber paper for electromagnetic shielding, wherein the carbon fiber paper is prepared according to the preparation method described in any one of the first aspects; the carbon fiber paper for electromagnetic shielding comprises: Carbon fiber, as a skeletal material; Regenerated cellulose fibers, as a skeletal reinforcement material; and, Microfibrillated carbon fills the grooves on the surface of the regenerated cellulose fibers to form conductive pathways; The microfibrillated carbon is at least partially embedded in the grooves of the regenerated cellulose fiber and is oriented along the axial direction of the regenerated cellulose fiber.

[0016] Furthermore, the microfibrillated carbon is distributed layer by layer along the groove depth direction in the grooves on the surface of the regenerated cellulose fibers, and the carbon filled in each round is in a partial covering state. In the next round of enzyme treatment, the carbon is peeled off in the area not covered by carbon towards the groove depth direction.

[0017] Furthermore, the regenerated cellulose fibers and the microfibrillated carbon are physically intercalated together; The carbon fiber paper for electromagnetic shielding comprises, by weight percentage: Carbon fiber 65-84%; Regenerated cellulose fiber 15-30%; and Microfiberized carbon 1-5%.

[0018] Thirdly, the present invention provides a wedge-shaped flow channel device for preparing carbon fiber paper for electromagnetic shielding. The wedge-shaped flow channel includes an inlet end and an outlet end. The flow channel spacing from the inlet end to the outlet end gradually changes from wide to narrow. The wedge-shaped flow channel is used to allow mixed slurry to pass through, so that the mixed slurry flowing through is subjected to a gradient-enhanced shear force, thereby aligning the microfibrillated carbon fibers therein along the axial direction of the regenerated cellulose fibers.

[0019] Beneficial effects

[0020] The method for preparing carbon fiber paper for electromagnetic shielding provided by this invention achieves the following beneficial effects through a synergistic process design of "stepwise enzyme treatment cycle + wedge-shaped flow channel shear-induced directional alignment": This method enables progressive deep embedding of carbon fibers through a multi-round "peeling-carbon filling" positive feedback loop. Each round begins with endonuclease peeling open the fiber cortex to expose fresh hydroxyl sites, followed by the introduction of microfibrillated carbon fibers to embed into the newly exposed grooves. In the next round of enzyme treatment, the embedded carbon fibers protect the peeled areas, allowing the enzyme to preferentially attack deeper, unprotected sites. This progressive approach deepens the embedding depth and filling density, far exceeding single-step treatment methods. Furthermore, this application employs a gentle, step-by-step treatment approach, starting with a low concentration and removing only the outermost amorphous region in each round, while immediately filling and protecting it with carbon fibers to avoid excessive hydrolysis. This effectively maintains the fiber's skeletal strength while achieving deep embedding. Enzyme treatment exposes more hydrophilic groups on the fiber surface, improving the fiber's dispersion in the aqueous system. Combined with wedge-shaped flow channel shearing-induced carbon fiber orientation, this achieves a synergistic improvement in the quantitative uniformity and conductivity of carbon fiber paper in the MD / TD direction.

[0021] The carbon fiber paper for electromagnetic shielding provided by this invention significantly improves conductivity. Microfibrillated carbon fibers are directly embedded in the grooves on the surface of regenerated cellulose fibers, rather than being bonded to the fiber surface by an insulating polymer adhesive. This creates direct contact conductive pathways between the carbon fibers, eliminating the need for an insulating layer to block electron transport paths. This results in a fundamental improvement in conductivity without the addition of any conductive additives. Furthermore, it stabilizes the conductive network structure. The carbon fibers are embedded within the fiber grooves, forming a mechanically interlocking structure, rather than simply adhering to the fiber surface. This embedded structure makes the carbon fibers less prone to detachment when the carbon fiber paper is subjected to bending or in high-humidity environments. The durability and environmental stability of the conductive network are significantly superior to traditional coating or blending methods. Moreover, the conductive pathways are continuous and ordered. The carbon fibers are oriented along the fiber axis, forming an "axially parallel" structure. This ordered arrangement makes the electron transport path more direct and less tortuous, further reducing the material's resistivity, while avoiding the resin encapsulation effect during subsequent drying and molding, ensuring the continuity of the conductive pathways. Attached Figure Description

[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0023] Figure 1 A schematic flowchart illustrating a method for preparing carbon fiber paper for electromagnetic shielding, provided for an embodiment of the present invention. Figure 2 A planar scanning electron microscope (SEM) image of a carbon fiber paper for electromagnetic shielding provided by the present invention 1; Figure 3 A schematic diagram of a wedge-shaped flow channel provided for an embodiment of the present invention; Figure 4 This is a comparison chart of the conductivity test results of Embodiment 1 and Comparative Example 5 of the present invention; Figure 5 This is a comparison chart of the electromagnetic shielding effectiveness (EMI SE) test results of Example 1 and Comparative Example 5 of the present invention. Detailed Implementation

[0024] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] In this invention, the terms "first," "second," etc., are used for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0026] It should be noted that if the embodiments of the present invention involve directional indicators (such as up, down, left, right, front, back, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a specific posture. If the specific posture changes, the directional indicators will also change accordingly.

[0027] Furthermore, the technical solutions of the various embodiments of the present invention can be combined with each other, but only if they are feasible for those skilled in the art. If the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.

[0028] To better understand the above technical solutions, the present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0029] This invention provides a method for preparing carbon fiber paper for electromagnetic shielding, such as... Figure 1 As shown, the method includes: Step S10: Mix regenerated cellulose fibers with microfibrillated carbon to obtain a mixed slurry; Step S20: Perform a stepwise enzymatic treatment on the mixed slurry, wherein the stepwise enzymatic treatment includes N cycles of enzymatic treatment and carbon filling, where N≥2, and each cycle includes: The regenerated cellulose fibers were treated with endonuclease to expose carboxyl and hydroxyl groups on the surface of the regenerated cellulose fibers. After the endonuclease treatment, microfibrillated carbon is added to the system so that the microfibrillated carbon is embedded in the grooves on the surface of the regenerated cellulose fibers. Step S30: The mixed slurry after the step-enzyme treatment is fed into a wedge-shaped channel, and the microfibrillated carbon is oriented along the axial direction of the regenerated cellulose fibers by using gradient-enhanced shear force. Step S40: Mix the mixed slurry after wedge channel treatment with carbon fiber slurry, form into shape, dry, and hot press to obtain carbon fiber paper for electromagnetic shielding.

[0030] In this embodiment of the invention, the regenerated cellulose fiber used is a robust fiber with an average length of 5 mm, an average diameter of 1.7D, and a degree of polymerization of 600-800. Its source includes, but is not limited to, at least one of cotton linters, cotton pulp, wood pulp, or bamboo pulp. The regenerated cellulose fiber serves as a reinforcing skeleton (similar to "straw") for carbon fiber paper, providing mechanical support.

[0031] The microfibrillated carbon used is a highly swellable carbon material with an average particle size of 10-15 nm, an aspect ratio >350, and a specific surface area >230 m² / g. It exhibits good swelling and dispersibility in aqueous systems. The microfibrillated carbon is selected from at least one of carbon nanotubes, graphene flakes, carbon fiber powder, and conductive carbon black, preferably multi-walled carbon nanotubes or graphene flakes with a high aspect ratio. It serves as a conductive matrix (similar to "mud") to provide conductivity.

[0032] The endonuclease (EG) used was selected from commercially available cellulase preparations, with an enzyme activity of 10-800 U / mL, an optimal pH of 4.0-6.0, and an optimal temperature of 25-40℃.

[0033] The preferred surfactant used is bio-based cashew sulfonate, which has a hydrophilic-lipophilic balance (HLB) of 9-11 and a critical micelle concentration of 2-4 mmol / L.

[0034] The carbon fiber used is selected from at least one of PAN-based carbon fiber, pitch-based carbon fiber, or viscose-based carbon fiber. Commercially available carbon fiber can be used. The carbon fiber is dispersed in deionized water to prepare a carbon fiber slurry with a mass concentration of 0.01-0.1 wt%. Preferably, the mass concentration of the carbon fiber slurry is 0.05 wt%. The dispersion method is at least one of mechanical stirring, ultrasonic dispersion, or high-speed shear dispersion, and the dispersion time is 10-20 min.

[0035] In the carbon fiber paper, carbon fibers serve as the main skeleton material, forming a three-dimensional interwoven conductive network structure. Regenerated cellulose fibers, as the skeleton reinforcement material, fill the spaces between the carbon fiber skeletons, enhancing the bonding force between the carbon fibers through hydrogen bonding and physical interweaving. Simultaneously, they act as the carrier matrix for the microfibrillated carbon, constructing fine conductive channels within the microscopic voids of the carbon fiber skeleton. The synergistic effect of these two materials forms a multi-scale structure of macroscopic skeleton (carbon fibers) + microscopic reinforcing skeleton (regenerated cellulose fiber / carbon composite). Figure 2 This is a planar scanning electron microscope (SEM) image of the carbon fiber paper of this invention. The straight, thicker fibers in the image are carbon fibers, while the curved, thin, and flexible fibers are Tencel fibers. As can be seen from the image, both types of fibers are evenly distributed within the paper sheet, with no obvious fiber agglomeration areas or blank areas, indicating good dispersion compatibility in the aqueous system. The carbon fibers maintain a relatively straight shape in the image, indicating that they did not undergo severe curling or damage during pulp dispersion. The Tencel fibers exhibit a naturally curved state, surrounding and distributing among the carbon fibers, with the two interwoven to form a relatively uniform fiber network. The curved Tencel fibers are wound around the surface of the carbon fibers or interwoven between the carbon fibers, forming a mechanically interwoven structure. This interweaving effect "locks" the carbon fibers within the paper sheet network, providing the carbon fiber paper with basic structural integrity and mechanical strength.

[0036] It should be noted that this figure reflects the interweaving state of carbon fibers and regenerated cellulose fibers on a macroscopic scale. The microfibrillated carbon embedding state, due to its nanoscale structure, is difficult to capture clearly with existing scanning electron microscope equipment and is therefore not shown in the image here.

[0037] In a preferred embodiment of the present invention, prior to the stepwise enzyme treatment, the regenerated cellulose fibers and microfibrillated carbon are first subjected to Zeta potential regulation, specifically including: The first stage—fiber surface charge regulation: Regenerated cellulose fibers are dispersed in deionized water to prepare a fiber suspension with a mass concentration of 0.77%. An enzyme, cellulase or hemicellulase, is added to the suspension for treatment at a dosage of 0.5 U / g oven-dry fiber. The treatment temperature is 45-55℃, the treatment time is 15-60 min, the pH is 4.5-5.5, and the stirring speed is 600 r / min. After this treatment, some amorphous regions on the surface of the regenerated cellulose fibers are removed, exposing more carboxyl and hydroxyl functional groups, giving the fiber surface a weak negative charge (Zeta potential of -10 mV to -20 mV). After treatment, the fibers are filtered and washed to remove residual oxidants or enzymes.

[0038] The second stage—carbon surface charge regulation: Microfibrillated carbon is dispersed in deionized water to prepare a carbon suspension with a mass concentration of 0.1%. A surfactant, preferably bio-based cashew sulfonate, is added to the suspension at an amount of 5% to 10% of the oven-dry mass of the carbon. By controlling the amount of surfactant added, the Zeta potential of the microfibrillated carbon is adjusted to near its isoelectric point (Zeta potential of -1.5mV to -3mV), placing the microfibrillated carbon in a critical state of slight flocculation. In this state, the electrostatic repulsion between microfibrillated carbon particles is weakened, allowing for slight reversible aggregation, but without forming irreversible severe agglomeration.

[0039] The regenerated cellulose fibers treated in the first stage were mixed with the microfibrillated carbon fibers treated in the second stage, and stirred for 20 to 40 minutes at a stirring speed of 500 rpm, followed by sonication for 30 minutes. During this mixing process, an electrostatic attraction was generated between the weakly negatively charged regenerated cellulose fibers and the microfibrillated carbon fibers, which were near their isoelectric points. This attraction drove the microfibrillated carbon fibers to actively migrate to the surface of the regenerated cellulose fibers and initially embed themselves in the grooves on the fiber surface. This electrostatic driving process essentially provides "positioning" and "initial fixation" for the carbon fibers at the microscale, laying the foundation for the progressively deeper embedding in subsequent stepwise enzymatic treatments.

[0040] The zeta potential-regulated mixed slurry is subjected to a stepwise enzymatic treatment, which includes N cycles of enzymatic treatment and carbon filling, where N ≥ 2. In a preferred embodiment of the invention, N = 3, specifically including the following three cycles: First cycle: Endocellulase (EG) is added to the mixed slurry at a concentration of 0.5-1.0 U / mL (relative to the total volume of the mixed slurry). The pH is adjusted to 5.0-5.5, the temperature is controlled at 25±2℃, and the treatment time is 10-15 min. Under these conditions, EG selectively hydrolyzes the most porous amorphous fragments on the surface of the regenerated cellulose fiber cortex, exposing some hydroxyl groups in the subsurface layer, while the main crystalline structure of the fiber is preserved. After the enzyme treatment, microfibrillated carbon is added to the system to bring the total concentration of microfibrillated carbon in the mixed slurry to 0.5 wt%, and stirring and filling are continued for 30±3 min. During this process, the microfibrillated carbon, which is in a slightly flocculated critical state, is further squeezed into the newly exposed fiber surface grooves under the drive of electrostatic attraction.

[0041] Second cycle: Endocellulase (EG) is added again to the mixed slurry after the first cycle, increasing the enzyme concentration to 2.0-3.0 U / mL, adjusting the pH to 4.8-5.2, controlling the temperature at 30±2℃, and the treatment time to 7-10 min. Under these conditions, since the microfibrillated carbon from the first cycle has already covered part of the fiber surface, the enzyme molecules cannot attack the protected areas covered by carbon. Therefore, they preferentially attack the exposed areas at the bottom and sidewalls of the trenches that are not covered by carbon, continuing to "dig" towards the fiber core, exposing more fresh hydroxyl groups. After the enzyme treatment, microfibrillated carbon is added again to bring the total concentration of microfibrillated carbon in the mixed slurry to 1.0 wt%, and stirring and filling continues for 20 min±3, allowing the carbon to embed into the newly exposed deeper trench sites.

[0042] Third cycle: Endocellulase (EG) is added again to the mixed slurry after the second treatment, further increasing the enzyme concentration to 5.0-8.0 U / mL, adjusting the pH to 4.5-4.8, controlling the temperature at 35±2℃, and the treatment time to 5-7 min. Under these conditions, the enzyme continues to attack the deeper exposed areas in the trenches that are not covered by carbon, further excavating towards the core layer. After the enzyme treatment, microfibrillated carbon is added again to bring the total concentration of microfibrillated carbon in the mixed slurry to 1.5 wt%, and stirring and filling continues for 10±3 min to allow the carbon to embed into the deepest trench sites.

[0043] After the above three cycles, a positive feedback loop of "stripping - carbon filling - re-stripping - re-carbon filling" is formed. After each round of treatment, the grooves on the fiber surface are continuously deepened, and the carbon embedding depth and density increase in each round, ultimately achieving the layer-by-layer distribution of microfibrillated carbon along the depth direction of the fiber grooves.

[0044] It should be noted that the enzyme concentration, treatment time, treatment temperature, pH value, carbon filling concentration and filling time in the first to third rounds mentioned above are all preferred embodiments of the present invention. Those skilled in the art can adjust the above parameters appropriately within a certain range according to the actual raw material conditions.

[0045] In other embodiments of the present invention, the number of cycles N in the stepwise enzyme treatment can also be 2, 4, or 5 cycles. With 2 cycles, only the first two cycles of the aforementioned 3 cycles can be used, increasing the enzyme concentration and treatment time in each cycle. When N>3, the enzyme concentration in the 4th and subsequent cycles can continue to increase in an incremental gradient (e.g., 8.0-12.0 U / mL), the treatment time can continue to decrease (e.g., 3-5 min), the carbon loading concentration can continue to increase (e.g., 2.0-3.0 wt%), and the loading time can continue to decrease (e.g., 5-8 min). The temperature in each cycle can continue to increase (e.g., 40±2℃), and the pH can continue to decrease (e.g., 4.2-4.5). Specific parameters can be determined by those skilled in the art through conventional experiments based on actual treatment results.

[0046] After each round of enzyme treatment reaches the set time, the enzyme reaction can be terminated by one of the following methods: (a) heating the system to 80-90°C and holding for 5-10 minutes to thermally inactivate the enzyme; (b) adjusting the pH of the system to above 9.0 or below 3.0 to inactivate the enzyme; (c) adding an enzyme inhibitor. In a preferred embodiment of the present invention, since carbon will physically adsorb with enzyme molecules in the subsequent carbon filling step, the activity of some enzymes has been inhibited. Therefore, no special termination is required, and the next round of filling can proceed directly. To ensure process controllability, it is recommended to use the heating termination method, raising the system temperature to 85°C, holding for 5 minutes, and then cooling to the set temperature for the next round.

[0047] The mixed slurry, after stepwise enzyme treatment, is fed into a wedge-shaped flow channel. The structure of the wedge-shaped flow channel is as follows: Figure 2 As shown, it includes an inlet end and an outlet end, and the channel spacing from the inlet end to the outlet end gradually and smoothly changes from wide to narrow. In a preferred embodiment of the present invention, the inlet width of the wedge-shaped channel is 60 mm, the outlet width is 30 mm, the channel length is 660 mm, and the channel contraction angle is 30 degrees.

[0048] The mixed slurry flows through the wedge-shaped channel at a velocity of 0.5 m / s to 1 m / s, driven by a delivery pump. As the channel cross-section gradually narrows from the inlet to the outlet, the slurry velocity gradually increases, and the shear rate exhibits a gradient enhancement. Under the combined action of the gradient-enhanced shear and tensile flows, the microfibrillated carbon fibers in the mixed slurry are driven by hydrodynamic torques and rotate, eventually stabilizing in an orientation along the flow direction (i.e., the axial direction of the regenerated cellulose fibers), forming an "axially aligned" structure similar to collagen in tendons.

[0049] The ratio of the inlet width to the outlet width of the wedge-shaped flow channel is preferably 2:1 to 3:1, and the contraction angle of the flow channel is preferably 15 degrees to 45 degrees, so as to ensure that the shear rate presents a smooth rather than abrupt gradient distribution along the flow channel direction.

[0050] The mixed slurry, after being sheared and oriented through a wedge-shaped flow channel, is shaped and dried to obtain electromagnetic shielding carbon fiber paper.

[0051] Forming: A wet forming process is employed, involving mixing the mixed slurry and carbon fiber slurry together and forming them on a paper forming machine. The forming mesh count is 80 mesh, the forming pressure is 2 MPa, and the forming time is 30 seconds. Wet forming is a conventional technique in the field and will not be described in detail here. In a preferred embodiment of the invention, the mixed slurry undergoes a slag removal and screening process before entering the forming machine to remove impurities and undispersed fiber bundles from the slurry.

[0052] Drying: The formed paper web is dried at a temperature of 120°C to 180°C for 3 to 10 minutes. The moisture content of the carbon fiber paper after drying is controlled below 5%. The drying method can be at least one of hot air drying, infrared drying, or vacuum drying. In a preferred embodiment of the invention, a segmented heating and drying method is used: the first stage is drying at 120°C for 3 minutes, the second stage at 150°C for 3 minutes, and the third stage at 180°C for 4 minutes. Segmented heating and drying helps avoid the problem of excessively rapid drying of the paper web surface, which prevents internal moisture from being discharged in time, thereby reducing paper web curling and deformation.

[0053] Hot pressing: The dried carbon fiber paper can also be hot-pressed at a pressure of 1-3 MPa and a temperature of 100-180℃. The thickness of the carbon fiber paper after hot pressing is 160-180 μm. Calendering can make the paper surface smoother and provide a certain strength, which is beneficial to the subsequent coating of electromagnetic shielding coating.

[0054] The method for preparing carbon fiber paper for electromagnetic shielding provided in the above-described specific embodiments of the present invention has the following technical effects: (1) Significantly improved conductivity. Through a step-by-step enzymatic treatment and a positive feedback loop of "stripping-carbon filling," microfibrillated carbon is embedded into the grooves on the surface of regenerated cellulose fibers in successive cycles. With each cycle, the carbon filling concentration increases (0.5wt%→1.0wt%→1.5wt%), and the embedding depth and filling density gradually increase, forming a continuous, dense, and directly contacting conductive pathway within the fiber grooves. No insulating polymer binder is added throughout the process, and there is no insulating layer blocking the conductive pathway, ensuring unobstructed electron transport. (2) Excellent wideband electromagnetic shielding performance. Due to the continuous three-dimensional conductive network formed by carbon in the fiber grooves and the directional arrangement of carbon along the fiber axis, the electron transmission has low tortuosity and direct path. This carbon fiber paper exhibits excellent electromagnetic shielding performance in a wideband range of L2 band (1.72-2.61GHz), S1 band (2.6-3.95GHz), S2 band (3.95-5.99GHz), C band (5.4-8.2GHz), X band (8.2-12.4GHz) and Ku band (12.5-18GHz), with an average EMISE of 30-40dB, which can meet the high requirements of applications such as precision instruments, electronic components and military industry.

[0055] (3) Improved fiber dispersion and uniformity. In the stepwise enzyme treatment, each round of enzyme treatment exposes more carboxyl and hydroxyl hydrophilic groups on the fiber surface, significantly improving the dispersion state of regenerated cellulose fibers in the aqueous system and avoiding the problem of poor uniformity caused by the high rigidity and easy flocculation of carbon fibers in traditional processes. At the same time, the wedge-shaped flow channel, as a fluid stabilizing device, effectively reduces turbulence and eddies in the slurry flow, making the distribution of carbon in the slurry more uniform and stable. The synergistic effect of the two results in a significant improvement in the basis uniformity of the final carbon fiber paper in the MD / TD direction.

[0056] (4) The main strength of the fiber is effectively protected. Traditional strong acid and strong alkali treatment or high-intensity single-step enzyme treatment will seriously damage the main structure of the fiber, resulting in a significant decrease in mechanical properties. This invention uses a gentle treatment method with low concentration starting and progressive treatment in each round, removing only the amorphous region of the outermost layer of the fiber cortex in each round. Combined with the immediate filling and protection of carbon, it effectively avoids excessive hydrolysis of the fiber. While achieving deep carbon embedding, it maintains the mechanical strength of the regenerated cellulose fiber skeleton to the maximum extent.

[0057] (5) Stable conductive network structure. Carbon is embedded inside the fiber grooves rather than just attached to the surface, forming a physical embedding and mechanical interlocking structure. This embedding structure makes it difficult for carbon to fall off when the carbon fiber paper is bent, wound or in a high humidity environment. The durability and environmental stability of the conductive network are significantly better than traditional coating or blending solutions.

[0058] (6) The process is green and environmentally friendly. This invention uses an aqueous dispersion system, eliminating the need for organic solvents; the enzyme treatment conditions are mild (30-40℃, pH 4.5-5.5), resulting in low energy consumption; the entire process does not involve high-temperature graphitization (comparative document CN115287941B requires high-temperature treatment at 600-800℃), and the carbon intercalation process can be completed at room temperature and pressure. The entire process is green, environmentally friendly, and low-cost, making it suitable for large-scale industrial production.

[0059] The present invention also provides a carbon fiber paper for electromagnetic shielding, which is prepared according to the aforementioned preparation method. The carbon fiber paper for electromagnetic shielding comprises: carbon fibers as a skeleton material; regenerated cellulose fibers as a skeleton reinforcement material; and microfibrillated carbon fibers filling grooves on the surface of the regenerated cellulose fibers to form conductive pathways; the microfibrillated carbon fibers are at least partially embedded within the grooves of the regenerated cellulose fibers and are oriented along the axial direction of the regenerated cellulose fibers.

[0060] In the context of this invention, the term "embedded" means that the microfibrillated carbon particles are at least partially embedded in the grooves on the surface of the regenerated cellulose fiber, rather than merely attached to the fiber surface.

[0061] The regenerated cellulose fibers serve as the reinforcing skeleton (i.e., "straw") of the carbon fiber paper, providing mechanical support. The regenerated cellulose fibers possess abundant hydroxyl functional groups, giving them good hydrophilicity and dispersibility in aqueous systems, which is beneficial for forming a uniform mixture with microfibrillated carbon.

[0062] In some embodiments of the present invention, the regenerated cellulose fibers are robust fibers with an average length of 1.0-5.0 mm, preferably 2.0-4.0 mm; an average diameter of 1-3D, preferably 1.5-2D; and a degree of polymerization of 300-1000, preferably 600-800. Appropriate fiber length and diameter contribute to the formation of a three-dimensional interwoven network skeleton structure, providing sufficient mechanical strength and structural stability for the carbon fiber paper. If the fibers are too short or too thin, the number of interlacing points in the skeleton network decreases, resulting in insufficient mechanical strength; if the fibers are too long or too thick, the interlacing between the fibers is too tight, reducing porosity and hindering subsequent carbon filling and electron transport.

[0063] The regenerated cellulose fibers are sourced from at least one of the following: cotton linters, cotton pulp, wood pulp, bamboo pulp, and hemp pulp. In a preferred embodiment of the invention, cotton linters, cotton pulp, or wood pulp are selected because their fiber length distribution is uniform and their impurity content is low, which is beneficial for forming high-quality carbon fiber paper.

[0064] The microfibrillated carbon is a highly swellable carbon material used as a conductive matrix. It fills the grooves on the surface of regenerated cellulose fibers to form conductive pathways. The microfibrillated carbon exhibits good swelling and dispersibility in aqueous systems, allowing it to be introduced into the fiber grooves in each cycle of a stepwise enzyme treatment, forming a conductive network distributed layer by layer along the groove depth.

[0065] In some embodiments of the present invention, the average particle size of the microfibrillated carbon is 1-20 nm, preferably 10-15 nm; the aspect ratio is 10:1 to 1000:1, preferably 50:1 to 500:1; and the specific surface area is 50-500 m² / g, preferably 100-300 m² / g. A higher aspect ratio is beneficial for the carbon to form a continuous network structure in the fiber grooves and to achieve directional alignment along the fiber axis under the shearing action of the wedge-shaped flow channel.

[0066] The microfibrillated carbon is selected from at least one of carbon nanotubes, graphene microsheets, carbon fiber powder, and conductive carbon black, preferably multi-walled carbon nanotubes or graphene microsheets with a high aspect ratio. In a preferred embodiment of the invention, multi-walled carbon nanotubes are used as the microfibrillated carbon, wherein the mass ratio of multi-walled carbon nanotubes to graphene microsheets is 1:1 to 3:2. Multi-walled carbon nanotubes are responsible for constructing one-dimensional conductive pathways, while graphene microsheets are responsible for forming two-dimensional conductive networks. Their synergistic effect allows for the construction of a more continuous and efficient three-dimensional conductive network within the fiber grooves.

[0067] The microfibrillated carbon is at least partially embedded within the grooves of the regenerated cellulose fibers. This embedded structure is formed through a step-by-step "stripping-carbon filling" process in a series of enzymatic treatment cycles. Specifically, each enzymatic treatment first strips away the outermost amorphous region of the fiber cortex, exposing new groove sites. Subsequently, the introduced microfibrillated carbon is "squeezed" into the newly exposed grooves under electrostatic attraction. After multiple cycles, the carbon is distributed layer by layer along the groove depth, forming an embedded structure that is tightly bound to the fiber body.

[0068] This embedded structure enables a physical-mechanical interlock between the microfibrillated carbon and the regenerated cellulose fibers, rather than relying on chemical crosslinking agents or polymer binders for adhesion.

[0069] Compared with the prior art of coating or attaching carbon materials only to the fiber surface, the embedded structure of the present invention has the following advantages: (1) the bonding force between carbon and fiber is stronger, and it is not easy to fall off during stress or bending, and the durability of the conductive network is higher; (2) after carbon is embedded in the fiber, the fiber and carbon form an integrated structure, and the interface thermal resistance and interface resistance are lower; (3) the embedded structure reduces the exposure of carbon on the outer surface of the fiber, and reduces the risk of carbon being oxidized or contaminated in subsequent use.

[0070] The microfibrillated carbon fibers are oriented along the axial direction of the regenerated cellulose fibers. This oriented arrangement is achieved through a wedge-shaped flow channel shear-induced process. Specifically, when the mixed slurry flows through a wedge-shaped flow channel with a gradually narrowing spacing, it is subjected to gradient-enhanced shear and stretching flows. Driven by hydrodynamic torque, the microfibrillated carbon fibers rotate and eventually stabilize in an orientation along the flow direction (i.e., the axial direction of the regenerated cellulose fibers).

[0071] This oriented alignment structure enables the microfibrillated carbon fibers to form ordered conductive channels within the carbon fiber paper. Electrons travel along the axial direction via a more direct and less tortuous path, significantly reducing the resistivity of the carbon fiber paper. Simultaneously, the oriented alignment structure effectively avoids the lateral encapsulation effect of the resin during subsequent drying and molding—when the carbon fibers are orderly aligned along the fiber axis, resin molecules tend to spread laterally along the fiber surface rather than longitudinally during drying. This ensures that the carbon surface maintains sufficient exposed area, preventing the conductive pathways from being completely blocked by the insulating layer.

[0072] In some embodiments of the present invention, the regenerated cellulose fibers and the microfibrillated carbon are physically intercalated and do not contain insulating polymer binders as the main component.

[0073] "Physical embedding bonding" refers to the bonding between regenerated cellulose fibers and microfibrillated carbon through mechanical interlocking and physical adsorption, rather than through chemical cross-linking agents, polymer binders, or other chemical bonding methods. Specifically, after the microfibrillated carbon is embedded in the fiber grooves, the sidewalls of the grooves physically bind the carbon particles. Simultaneously, van der Waals forces and electrostatic interactions exist between the carbon and the fiber, working together to firmly fix the carbon within the grooves. This bonding method does not rely on any external insulating material.

[0074] "Not containing insulating polymer binders as main components" means that the carbon fiber paper of the present invention does not contain insulating polymers commonly used in traditional papermaking processes, such as polyvinyl alcohol (PVA), polyvinyl acetate (PVAc), styrene-butadiene rubber (SBR), and polyacrylate, as binder components to reinforce fibers or fix conductive fillers. It should be understood that the carbon fiber paper of the present invention may contain trace amounts of impurities that are unavoidably introduced during the preparation process, but these impurities are not actively added as binder components, and their content is typically less than 1-2% of the total mass of the carbon fiber paper.

[0075] Compared with existing technologies, this invention achieves carbon fixation through physical embedding, eliminating the need for insulating adhesives and thus avoiding the problem of adhesives covering the carbon surface and blocking electron transport channels. This is one of the key reasons why the carbon fiber paper of this invention can achieve high conductivity.

[0076] In some embodiments of the present invention, the carbon fiber paper for electromagnetic shielding comprises, by weight percentage, the following components: Carbon fiber 65-84%; Regenerated cellulose fiber: 15% to 30%; Microfiberized carbon: 1% to 5%.

[0077] In a preferred embodiment of the present invention, the mass ratio of the regenerated cellulose fiber to the microfibrillated carbon is 7:1 to 8:1. Within this mass ratio range, carbon fiber paper can simultaneously achieve good mechanical and electrical properties. If the proportion of regenerated cellulose fiber is too high, the electrical conductivity and electromagnetic shielding effectiveness of the carbon fiber paper are insufficient; if the proportion of microfibrillated carbon is too high, the mechanical strength of the carbon fiber paper decreases and its brittleness increases.

[0078] Physical and performance characteristics of the product

[0079] In some embodiments of the present invention, the carbon fiber paper for electromagnetic shielding has the following characteristics: (1) Thickness: The thickness of the carbon fiber paper is 150μm to 400μm, preferably 180μm to 300μm. The thickness can be measured by a paper thickness measuring instrument according to GB / T 451.3 standard.

[0080] (2) Basis weight: The basis weight of the carbon fiber paper is 15 g / m² to 40 g / m², preferably 18 g / m² to 30 g / m². The basis weight can be obtained by weighing with an electronic balance and then calculating based on the area.

[0081] (3) Electrical conductivity: The electrical conductivity of the carbon fiber paper is 1600 S / cm to 2300 S / cm. The electrical conductivity was measured by the four-probe method according to GB / T 1552 standard. This electrical conductivity level is comparable to or better than that of carbon fiber paper prepared by traditional latex coating process.

[0082] (4) Electromagnetic shielding effectiveness: The average electromagnetic shielding effectiveness (EMI SE) of the carbon fiber paper in the L2 band (1.72-2.61GHz), S1 band (2.6-3.95GHz), S2 band (3.95-5.99GHz), C band (5.4-8.2GHz), X band (8.2-12.4GHz), and Ku band (12.5-18GHz) is 30-40dB. The electromagnetic shielding effectiveness is measured according to GB / T 30142 standard using the coaxial method or waveguide method. This wide-band shielding effectiveness enables the carbon fiber paper of the present invention to meet the high-requirement requirements of applications such as precision instruments, electronic components, and military industries.

[0083] The carbon fiber paper for electromagnetic shielding provided by this invention can serve as a base layer for electromagnetic shielding paper and is widely used in the following fields: electromagnetic shielding packaging of precision instruments, electromagnetic interference protection of electronic components, high-reliability electromagnetic shielding of military equipment, outer shell shielding layers of communication equipment, and electromagnetic compatibility (EMC) components of new energy vehicle electronic control systems. Due to its lightweight, flexibility, high conductivity, excellent wide-band shielding effectiveness, and lack of insulating adhesives, it is particularly suitable for wearable electronic devices, flexible displays, and lightweight electromagnetic shielding components in the aerospace field where strict requirements for weight and flexibility are necessary.

[0084] This invention also provides a wedge-shaped flow channel device for preparing carbon fiber paper for electromagnetic shielding, such as... Figure 3 As shown, the wedge-shaped flow channel includes an inlet end and an outlet end. The flow channel spacing from the inlet end to the outlet end gradually changes from wide to narrow. The wedge-shaped flow channel is used to allow the mixed slurry to pass through, so that the flowing mixed slurry is subjected to a gradient-enhanced shear force, thereby aligning the microfibrillated carbon in it along the axial direction of the regenerated cellulose fibers.

[0085] To further illustrate the effect of the dosage of each key component in this embodiment on the performance of carbon fiber paper used for electromagnetic shielding, carbon fiber papers prepared in Examples 1 to 6 and Comparative Examples 1 to 5 as shown below are provided and tested.

[0086] Example 1

[0087] (1) Raw material preparation: Carbon fiber: PAN-based carbon fiber, with an average length of 6 mm and an average diameter of 7 μm.

[0088] Regenerated cellulose fiber: cotton linter pulp, average length 5mm, average diameter 1.7D (approximately 18μm), degree of polymerization 700.

[0089] Microfibrillated carbon: a mixture of multi-walled carbon nanotubes and graphene microsheets (mass ratio 3:2), with an average particle size of 12 nm, an aspect ratio of >350, and a specific surface area of ​​>230 m² / g.

[0090] Endocellulase (EG): Commercially available, enzyme activity 400 U / mL, optimal pH 5.0, optimal temperature 35℃.

[0091] Surfactant: Bio-based cashew sulfonate, HLB value 10, critical micelle concentration 3 mmol / L.

[0092] (2) Preparation of carbon fiber slurry: PAN-based carbon fibers were dispersed in deionized water to prepare a carbon fiber slurry with a mass concentration of 0.05 wt%. The slurry was then mechanically stirred for 30 minutes at a stirring speed of 800 rpm to ensure that the carbon fibers were uniformly dispersed in monofilament form without obvious agglomeration. The resulting carbon fiber slurry was then ready for use.

[0093] (3) Staged regulation of Zeta potential: The first stage—fiber surface charge regulation: Regenerated cellulose fibers were dispersed in deionized water to prepare a fiber suspension with a mass concentration of 0.77%. Cellulase was added to the suspension for treatment at a dosage of 0.5 U / g oven-dry fiber, a treatment temperature of 50°C, a treatment time of 30 min, a pH of 5.0, and a stirring speed of 600 r / min. After this treatment, some amorphous regions on the surface of the regenerated cellulose fibers were removed, exposing more carboxyl and hydroxyl functional groups, giving the fiber surface a weak negative charge (Zeta potential of -15 mV). The fibers were then filtered and washed to remove residual enzyme.

[0094] The second stage—carbon surface charge regulation: Microfibrillated carbon was dispersed in deionized water to prepare a carbon suspension with a mass concentration of 0.1%. Bio-based cashew sulfonate was added to the suspension, with the amount of surfactant added being 7% of the oven-dry mass of the carbon. By controlling the amount of surfactant added, the Zeta potential of the microfibrillated carbon was adjusted to near the isoelectric point (Zeta potential is -2mV), bringing the microfibrillated carbon to a critical state of slight flocculation.

[0095] Mixing: The regenerated cellulose fibers treated in the first stage and the microfibrillated carbon fibers treated in the second stage were mixed at an oven-dry mass ratio of 88:12, stirred for 30 minutes at a stirring speed of 500 rpm, and then sonicated for another 30 minutes. During this mixing process, the weakly negatively charged regenerated cellulose fibers and the microfibrillated carbon fibers, which are near their isoelectric points, generate electrostatic attraction, driving the microfibrillated carbon fibers to actively migrate to the surface of the regenerated cellulose fibers and initially embed themselves in the grooves on the fiber surface.

[0096] (4) Stepwise enzyme treatment (3 cycles): First cycle: Endocellulase (EG) was added to the mixed slurry at a concentration of 0.8 U / mL (relative to the total volume of the mixed slurry), the pH was adjusted to 5.2, the temperature was controlled at 25℃, and the treatment time was 12 min. Under these conditions, EG selectively hydrolyzed the most porous amorphous fragments on the surface of the regenerated cellulose fiber cortex, exposing some hydroxyl groups in the subsurface layer, while the main crystalline structure of the fiber was preserved. After the enzyme treatment, microfibrillating carbon was added to the system to bring the total concentration of microfibrillating carbon in the mixed slurry to 0.5 wt%, and stirring and filling were continued for 30 min. During this process, the microfibrillating carbon, which was in a slightly flocculated critical state, was further squeezed into the newly exposed fiber surface groove sites driven by electrostatic attraction during the first round of enzyme treatment.

[0097] Second cycle: Endocellulase (EG) was added again to the mixed slurry after the first treatment, increasing the enzyme concentration to 2.5 U / mL. The pH was adjusted to 5.0, the temperature was controlled at 30℃, and the treatment time was 8 min. After the enzyme treatment, microfibrillated carbon was added again to bring the total concentration of microfibrillated carbon in the mixed slurry to 1.0 wt%. Stirring and filling continued for 20 min to allow the carbon to embed into the newly exposed deeper trench sites.

[0098] Third cycle: Endocellulase (EG) was added again to the mixed slurry after the second treatment, further increasing the enzyme concentration to 6.0 U / mL. The pH was adjusted to 4.6, the temperature was controlled at 35℃, and the treatment time was 6 min. Under these conditions, the enzyme continued to attack the deeper exposed areas in the trenches that were not covered by carbon, further excavating towards the core layer. After the enzyme treatment, microfibrillated carbon was added again to bring the total concentration of microfibrillated carbon in the mixed slurry to 1.5 wt%. Stirring and filling continued for 10 min to allow the carbon to embed into the deepest trench sites.

[0099] After each round of enzyme treatment reaches the set time, the enzyme is thermally inactivated by heating termination method (heating the system to 85℃ and holding for 5 minutes).

[0100] (5) Wedge-shaped flow channel shear-induced directional alignment: The mixed slurry, after stepwise enzyme treatment, is fed into a wedge-shaped flow channel. The wedge-shaped flow channel has an inlet width of 60 mm, an outlet width of 30 mm, a length of 660 mm, and a contraction angle of 30 degrees. The mixed slurry flows through the wedge-shaped flow channel at a velocity of 0.8 m / s driven by a delivery pump.

[0101] (6) Mixing and molding: The regenerated cellulose / microfibrillated carbon mixed slurry, after being treated with a wedge-shaped flow channel, was mixed with the prepared carbon fiber slurry to achieve an oven-dry mass ratio of carbon fiber:regenerated cellulose fiber:microfibrillated carbon fiber = 75:22:3. The mixture was stirred for 20 minutes at a stirring speed of 600 rpm.

[0102] The mixed pulp is wet-formed on a paper forming machine with a forming wire of 80 mesh, a forming pressure of 2 MPa, and a forming time of 30 seconds. The formed wet paper web is then dewatered by pressing at a pressure of 2 MPa for 5 minutes.

[0103] The pressed paper web was dried in stages at varying temperatures: the first stage was at 120℃ for 3 minutes, the second stage at 150℃ for 3 minutes, and the third stage at 180℃ for 4 minutes. The moisture content of the dried carbon fiber paper was controlled below 5%. This yielded carbon fiber paper suitable for electromagnetic shielding, which was then hot-pressed to give it a certain strength.

[0104] Example 2

[0105] The difference from Example 1 is that in the stepwise enzyme treatment, the enzyme concentration, treatment temperature, treatment time, and pH value are adjusted to the lower limit of the range.

[0106] Specifically: In the first cycle, the enzyme concentration was 0.5 U / mL, the treatment temperature was 23°C, the treatment time was 15 min, and the pH was 5.5; in the second cycle, the enzyme concentration was 2.0 U / mL, the treatment temperature was 28°C, the treatment time was 10 min, and the pH was 5.2; in the third cycle, the enzyme concentration was 5.0 U / mL, the treatment temperature was 33°C, the treatment time was 7 min, and the pH was 4.8. All other conditions were the same as in Example 1.

[0107] Example 3

[0108] The difference from Example 1 is that in the stepwise enzyme treatment, the enzyme concentration, treatment temperature, treatment time, and pH value are adjusted to the upper limit of the range.

[0109] Specifically: In the first cycle, the enzyme concentration was 1.0 U / mL, the treatment temperature was 27°C, the treatment time was 10 min, and the pH was 5.0; in the second cycle, the enzyme concentration was 3.0 U / mL, the treatment temperature was 32°C, the treatment time was 7 min, and the pH was 4.8; in the third cycle, the enzyme concentration was 8.0 U / mL, the treatment temperature was 37°C, the treatment time was 5 min, and the pH was 4.5. All other conditions were the same as in Example 1.

[0110] Example 4

[0111] The difference from Example 1 is that the number of stepwise enzyme treatment cycles N=4.

[0112] Specifically: the first to third cycles were the same as in Example 1; in the fourth cycle, the enzyme concentration was 10.0 U / mL, the treatment temperature was 40°C, the treatment time was 4 min, the pH was 4.3, and after enzyme treatment, microfiberized carbon was added to bring the total concentration to 2.0 wt%, with a filling time of 8 min. The final oven-dry mass ratio of the three components remained unchanged (carbon fiber: regenerated cellulose fiber: microfiberized carbon = 75:22:3). All other conditions were the same as in Example 1.

[0113] Example 5

[0114] The difference from Example 1 is that the oven-dry mass ratio of the three components is adjusted to carbon fiber: regenerated cellulose fiber: microfiberized carbon = 70:26:4. All other conditions are the same as in Example 1.

[0115] Example 6

[0116] The difference from Example 1 is that the outlet width of the wedge-shaped flow channel is adjusted to 35 mm (the inlet width remains unchanged at 60 mm), and the flow channel contraction angle is approximately 24°. All other conditions are the same as in Example 1. Comparative Example 1

[0117] Comparative Example 1

[0118] The difference from Example 1 is that the step-by-step enzyme treatment steps are omitted, and only a single-step enzyme treatment is used.

[0119] Specifically: Regenerated cellulose fibers and microfibrillated carbon were mixed at an oven-dry mass ratio of 88:12, and then subjected to a single enzyme treatment (enzyme concentration 0.8 U / mL, pH 5.2, temperature 25°C, treatment time 12 min). Then, all the microfibrillated carbon was added at once (to achieve a total concentration of 1.5 wt%), and the mixture was stirred and filled for 60 min. This mixture was then combined with carbon fiber slurry (the mass ratio of the three components remained unchanged: carbon fiber:regenerated cellulose fiber:microfibrillated carbon = 75:22:3), with all other conditions (including wedge channel treatment, molding, drying, etc.) the same as in Example 1.

[0120] Comparative Example 2

[0121] The difference from Example 1 is that the wedge-shaped flow channel shear-induced directional arrangement step is omitted.

[0122] Specifically: the mixed slurry after stepwise enzyme treatment is mixed with the carbon fiber slurry, and then directly molded and dried without undergoing wedge channel treatment. The remaining conditions are the same as in Example 1.

[0123] Comparative Example 3

[0124] The difference from Example 1 is that the enzyme concentration in each round of the stepwise enzyme treatment does not increase (each round is 0.8 U / mL), the carbon loading concentration does not increase (each round is 0.5 wt%), and the treatment time is not shortened (each round is 12 min). All other conditions are the same as in Example 1.

[0125] Comparative Example 4

[0126] The difference from Example 1 is that the Zeta potential regulation step is omitted.

[0127] Specifically: Unpotentially regulated regenerated cellulose fibers, carbon fibers, and microfibrillated carbon were directly mixed (the mass ratio of the three components remained unchanged, carbon fiber:regenerated cellulose fiber:microfibrillated carbon = 75:22:3) and then subjected to stepwise enzymatic treatment. The remaining conditions were the same as in Example 1.

[0128] Comparative Example 5 (Latex Coating Process)

[0129] Electromagnetic shielding carbon fiber paper was prepared using a traditional latex coating process. Specifically, using carbon fiber paper as the matrix, a coating was prepared by mixing conductive filler (a mixture of carbon nanotubes and graphene microsheets) and acrylic resin binder at a mass ratio of 2:1. The coating was then applied to the carbon fiber paper using a coating method and cured at 180°C for 10 minutes.

[0130] Performance testing methods

[0131] 1. Conductivity test

[0132] The four-probe method (RTS-8 four-probe tester) was used to determine the conductivity according to GB / T 1552 standard. Carbon fiber paper samples were cut into 20mm × 20mm square specimens. Four equally spaced probes were placed near the four corners of the specimen, a constant current was applied, and the potential difference was measured to calculate the conductivity (unit: S / m). Five different locations were tested on each sample, and the average value was taken.

[0133] 2. Electromagnetic Shielding Effectiveness (EMI SE) Test

[0134] Electromagnetic shielding effectiveness (in dB) was measured using a vector network analyzer (Agilent N5230A) according to GB / T 30142 standard, employing the waveguide method. Carbon fiber paper samples were cut into rectangular specimens of 22.9 mm × 10.2 mm and placed in a waveguide sample holder. Electromagnetic shielding effectiveness was tested in the following frequency ranges: L2 band (1.72-2.61 GHz), S1 band (2.6-3.95 GHz), S2 band (3.95-5.99 GHz), C band (5.4-8.2 GHz), X band (8.2-12.4 GHz), and Ku band (12.5-18 GHz). Each sample was tested three times, and the average value for each frequency band was recorded.

[0135] 3. Tensile strength test

[0136] According to GB / T 12914 standard, the test was conducted using a universal testing machine. Carbon fiber paper samples were cut into strips of 15mm × 70mm, with a clamping distance of 50mm and a tensile rate of 50mm / min. The maximum tensile force at break was recorded, and the tensile strength (unit: MPa) was calculated. Five samples were tested for each sample, and the average value was taken.

[0137] 4. Quantitative homogeneity test in the MD / TD direction

[0138] Ten points were taken at equal intervals along the MD direction (longitudinal) and TD direction (transverse) of the carbon fiber paper (each sampling area was 100 cm²). The quantitative value (g / m²) of each point was calculated after weighing with an electronic balance. The coefficient of variation (CV) of the quantitative value in the MD direction and TD direction was calculated respectively. The smaller the CV value, the better the uniformity.

[0139] The results of performance tests on the various embodiments and comparative examples are shown in Table 1 below.

[0140] Table 1: Performance test results of various embodiments and comparative examples

[0141] Data Analysis

[0142] (1) Conductivity data analysis

[0143] The conductivity test results show that Example 1 achieved a conductivity of 1980 S / m, an improvement of approximately 23.8% compared to the unoptimized process (1610 S / m). See also... Figure 4 , Figure 4 The figure shows a comparison of the conductivity test results of Example 1 and Comparative Example 5 of the present invention. In the figure, process 1 is the optimized process in Example 1, and process 2 is the existing latex coating process. It can be seen that the conductivity of carbon fiber paper is significantly improved by the optimized process of the present invention.

[0144] The conductivity of Examples 1-6 ranged from 1650 to 2550 S / m, all significantly better than the comparative examples. Example 4 exhibited the highest conductivity (2320 S / m), indicating that more stripping-carbon filling cycles facilitated the construction of a more complete conductive network, although tensile strength decreased. Example 3 (with parameters at their upper limits) showed a conductivity of 2150 S / m, indicating that higher enzyme and carbon filling concentrations improved conductivity.

[0145] The conductivity of Comparative Example 1 was only 1020 S / m, indicating that single-step enzyme treatment could not achieve layer-by-layer embedding of carbon along the trench depth direction, resulting in weak binding; single-step enzyme treatment plus one-time filling failed to effectively embed carbon, and the conductive pathway was discontinuous. The conductivity of Comparative Example 2 was 1280 S / m, significantly lower than that of Example 1, indicating that the tortuosity of the conductive pathway of carbon without shearing and orientation increased. The conductivity of Comparative Example 3 was 1050 S / m, further demonstrating the necessity of progressive parameter design. The conductivity of Comparative Example 4 was 1420 S / m, indicating that the carbon embedding efficiency decreased when electrostatic driving force was lacking. Comparative Example 5, due to the presence of acrylic resin binder, had the highest tensile strength (58.4 MPa) and a conductivity of 1610 S / m, but its EMI SE was only 26.0 dB, far lower than the 38.5 dB of Example 1, and its CV values ​​in the MD / TD directions were as high as 12.5% ​​and 14.2%, respectively. This indicates that the coating process has serious deficiencies in electromagnetic shielding effectiveness and uniformity, making it difficult to meet the requirements of high-precision electromagnetic shielding applications. Comparative Examples 1-4, lacking a key step of this application, all exhibit lower conductivity than existing coating processes (1610 S / m). This demonstrates that the various technical features of this invention have a synergistic effect, and none can be omitted.

[0146] (2) Electromagnetic shielding effectiveness data analysis

[0147] The EMI SE range of Examples 1-6 is 34.2-44.8 dB, with Example 5 having the highest (44.8 dB) and Example 2 having the lowest (34.2 dB).

[0148] The EMI SE of Comparative Examples 1-5 was lower than that of Examples 1-6, see [link / reference] Figure 5 , Figure 5The graph shows a comparison of the electromagnetic shielding effectiveness (EMI SE) test results between Example 1 and Comparative Example 5. Process 1 is Example 1, and Process 2 is Comparative Example 5. It can be seen that the carbon fiber paper prepared in Example 1 achieved an average electromagnetic shielding effectiveness (EMI SE) of 30-40 dB in the L2 (1.72~2.61GHz), S1 (2.6~3.95GHz), S2 (3.95~5.99GHz), C (5.4~8.2GHz), X (8.2~12.4GHz), and Ku (12.5~18GHz) bands, which is better than the carbon paper prepared by the unmodified process route (latex coating process).

[0149] EMI SE is positively correlated with electrical conductivity—the higher the conductivity, the higher the EMI SE. This is because higher conductivity means that the material has a more complete conductive network, resulting in more significant reflection and absorption losses of electromagnetic waves.

[0150] (3) Analysis of mechanical properties and uniformity data

[0151] The tensile strengths of Examples 1-6 ranged from 4 to 9 MPa, all of which were superior to Comparative Example 1 (4.2 MPa) and slightly lower than Comparative Example 5 (9.4 MPa). Among them, Comparative Example 5 (conventional coating process) had the highest tensile strength (9.4 MPa) because it contained a large amount of acrylic resin binder. However, this binder also caused a significant decrease in electrical conductivity and shielding effectiveness (580 S / m and 18.2 dB, respectively).

[0152] The CV value in the MD direction of Example 1 was 2.8%, and the CV value in the TD direction was 3.2%, while those in Comparative Example 5 were 12.5% ​​and 14.2%, respectively. This indicates that the present invention significantly improves the uniformity of carbon fiber paper by improving fiber dispersibility through stepwise enzyme treatment and combining it with the flow stabilization effect of wedge-shaped channels.

[0153] (4) Overall Conclusion

[0154] The comparative data of the above embodiments and comparative examples fully demonstrate that the present invention, through a three-in-one synergistic technical solution of "staged regulation of Zeta potential + stepwise enzyme treatment cycle + wedge-shaped flow channel shear-induced directional arrangement", achieves the layer-by-layer deep embedding and directional arrangement of microfibrillated carbon in the grooves of regenerated cellulose fibers and along the fiber axis. Without the need to add insulating polymer binders, the electrical conductivity of carbon fiber paper reaches 1980 S / m (an improvement of about 23.8% compared with the previous method), and the broadband EMI SE reaches 30-44.8 dB. At the same time, it maintains good mechanical properties (tensile strength 4.2-8.3 MPa) and excellent uniformity (CV values ​​in both MD and TD directions are less than 4.1%), achieving unexpected technical results.

[0155] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention specification and drawings under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.

[0156] It should be noted that when numerical ranges are involved in this invention, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, preferred embodiments are described in order to avoid redundancy. Although preferred embodiments of this invention have been described, those skilled in the art can make other changes and modifications to these embodiments once they know the basic inventive concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of this invention.

[0157] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from the spirit and scope of this invention; if these modifications and variations of this invention fall within the scope of the claims of this invention and their equivalents, then this invention also intends to include these modifications and variations.

Claims

1. A method for preparing carbon fiber paper for electromagnetic shielding, characterized in that, include: Regenerated cellulose fibers are mixed with microfibrillated carbon to obtain a mixed slurry; The mixed slurry is subjected to a stepwise enzymatic treatment, which includes N cycles of enzymatic treatment and carbon filling, where N ≥ 2, and each cycle includes: The regenerated cellulose fibers were treated with endonuclease to expose carboxyl and hydroxyl groups on the surface of the regenerated cellulose fibers. After the endonuclease treatment, microfibrillated carbon is added to the system so that the microfibrillated carbon is embedded in the grooves on the surface of the regenerated cellulose fibers. The mixed slurry after the stepwise enzyme treatment is fed into a wedge-shaped channel, where the gradient-enhanced shear force causes the microfibrillated carbon to align along the axial direction of the regenerated cellulose fibers. The mixed slurry, after being treated with a wedge-shaped flow channel, is mixed with carbon fiber slurry, then formed, dried, and hot-pressed to obtain carbon fiber paper for electromagnetic shielding.

2. The preparation method according to claim 1, characterized in that, In the stepwise enzyme treatment, the enzyme concentration increases from round 1 to round N, the treatment time decreases from round 1 to round N, and the concentration of microfibrillated carbon added after each round of enzyme treatment increases from round 1 to round N.

3. The preparation method according to claim 2, characterized in that, The stepwise enzyme treatment consists of 3 cycles: Round 1: Enzyme concentration is 0.5 to 1.0 U / mL, treatment temperature is 25±2℃, treatment time is 10 to 15 min, pH is 5.0 to 5.5, after enzyme treatment, add microfibrillated carbon to a concentration of 0.5 wt%, and fill time is 30±3 min; Round 2: The enzyme concentration is 2.0 to 3.0 U / mL, the treatment temperature is 30±2℃, the treatment time is 7 to 10 min, the pH is 4.8 to 5.2, and after enzyme treatment, microfibrillated carbon is added to a concentration of 1.0 wt%, with a filling time of 20±3 min. Round 3: Enzyme concentration of 5.0 to 8.0 U / mL, treatment temperature of 35±2℃, treatment time of 5 to 7 min, pH of 4.5 to 4.8, after enzyme treatment, add microfibrillated carbon to a concentration of 1.5 wt%, and fill time of 10±3 min.

4. The preparation method according to claim 1, characterized in that, Prior to the stepwise enzyme treatment, a step of regulating the Zeta potential in stages is also included, including: First stage: The regenerated cellulose fiber is pretreated with enzymes to expose carboxyl and hydroxyl groups on the surface of the regenerated cellulose fiber, thus imparting a weak negative charge. Second stage: The microfibrillated carbon is adjusted to near its isoelectric point using a surfactant, so that it is in a critical state of slight flocculation. Then, the regenerated cellulose fibers treated in the first stage are mixed with the microfibrillated carbon fibers treated in the second stage.

5. The preparation method according to claim 4, characterized in that, The surfactant is a bio-based cashew sulfonate.

6. The preparation method according to claim 1, characterized in that, The spacing of the wedge-shaped channels gradually changes from wide to narrow. When the mixed slurry flows through the wedge-shaped channels, it is subjected to a gradient-enhanced shear force, causing the microfibrillated carbon to be oriented along the axial direction of the regenerated cellulose fibers, forming an axially parallel structure.

7. The preparation method according to claim 1, characterized in that, The regenerated cellulose fiber is a robust fiber used as a reinforcing skeleton; the microfibrillated carbon is a highly swellable carbon used as a conductive matrix.

8. A carbon fiber paper for electromagnetic shielding, characterized in that, The carbon fiber paper is prepared by the preparation method according to any one of claims 1 to 7; the carbon fiber paper for electromagnetic shielding comprises: Carbon fiber, as a skeletal material; Regenerated cellulose fibers, as a skeletal reinforcement material; and, Microfibrillated carbon fills the grooves on the surface of the regenerated cellulose fibers to form conductive pathways; The microfibrillated carbon is at least partially embedded in the grooves of the regenerated cellulose fiber and is oriented along the axial direction of the regenerated cellulose fiber.

9. The carbon fiber paper for electromagnetic shielding according to claim 8, characterized in that, The regenerated cellulose fibers and the microfibrillated carbon are physically intercalated together. The carbon fiber paper for electromagnetic shielding comprises, by weight percentage: Carbon fiber 65-84%; Regenerated cellulose fiber 15-30%; and Microfiberized carbon 1-5%.

10. A wedge-shaped flow channel device for preparing carbon fiber paper for electromagnetic shielding, characterized in that, The wedge-shaped flow channel includes an inlet end and an outlet end, and the flow channel spacing from the inlet end to the outlet end gradually changes from wide to narrow. The wedge-shaped flow channel is used to allow the mixed slurry to pass through, so that the mixed slurry flowing through is subjected to a gradient-enhanced shear force, thereby aligning the microfibrillated carbon in it along the axial direction of the regenerated cellulose fibers.

Citation Information

Patent Citations

  • A method for preparing three-dimensional conductive carbon fiber paper

    CN115287941B

  • Carbon-based conductive paper film for electromagnetic shielding and preparation method thereof

    CN121653998A